Response to Training in Emotion Recognition Function for Mild TBI/PTSD Survivors: Pilot Study - J. Kay Waid-Ebbs; Kristen Lewandowski; Yi Zhang; Samantha Graham; Janis J. Daly (Brain Sciences)
Background/Objectives: For those with comorbid mild traumatic brain injury/post-traumatic stress disorder (mTBI/PTSD), deficits are common with regard to recognition of emotion expression in others. These deficits can cause isolation and suicidal ideation. For mTBI/PTSD, there is a dearth of information regarding effective treatment. In pilot work, we developed and tested an innovative treatment to improve recognition of both affect (facial expression of emotion) and prosody (spoken expression of emotion). Methods: We enrolled eight Veterans with mTBI/PTSD and administered eight treatment sessions. Measures included the following: Florida Affect Battery (FAB), a test of emotion recognition of facial affect and spoken prosody; Attention Index of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS); and Emotion Recognition Test (ERT), a speed test of facial emotion recognition. Results: There was a significant treatment response according to the FAB (p = 0.01, effect size = 1.2); RBANS attention index (p = 0.04, effect size = 0.99); and trending toward significance for the ERT (0.17, effect size 0.75). Participants were able to engage actively in all eight sessions and provided qualitative evidence supporting generalization of the training to interpersonal relationships. Conclusions: Our data show promising clinical potential and warrant future research, given the importance of developing novel interventions to train and restore recognition of emotion in Veterans with mTBI/PTSD.